A new species of genus Hoplobatrachus (Anura, Dicroglossidae) from the coastal belt of Bangladesh - Hasan, Mahmudul; Kuramoto, Mitsuru; Islam, Mohammed Mafizul; Alam, Mohammad Shafiqul; Khan, Md. Mukhlesur Rahman; Sumida, Masayuki (Zootaxa, 2012)
A new cryptic species of the genus Hoplobatrachus from Cox’s Bazar district of Bangladesh is described and compared with itsrelevant congeners both in morphology and mitochondrial gene sequences. The new species differs from its close relative H.tigerinus in having a distinct broad black band from the eye, through the nostrils, to the anterior edge of the upper jaw, anotherblack band along the lateral margin of the upper jaw, and a narrow inter-orbital distance relative to eyelid width and inter-nostrildistance. Advertisement calls of the new species are similar to those of H. tigerinus but differ in dominant frequency and num-ber of pulses. Based on mitochondrial DNA sequence data, this species was proved to genetically divergent from H. tigerinus at3.2% for the 16S rRNA gene and 14.2% for the Cytb gene. The known distribution range of the new species is restricted to the southeastern corner of Bangladesh and it seems to be endemic in this coastal belt.